Survey of motivation for use of voluntary counseling and testing services for HIV in a high risk area of Shenyang, China - Tian Jing; Fan Lijuan; Guo Junqiao; Zhou Ling; Zhou Baosen (BMC, 2009)
Abstract Background HIV voluntary counseling and testing (VCT) is considered an effective prevention method of HIV infection. In order to understand the VCT environment and enhance the effective delivery of VCT services in a country, an accurate assessment of the current status of VCT services is very important. Methods From July 2006 to June 2007, we conducted a cross-sectional survey using a face to face interview among 2676 VCT clients from a high risk area in Shenyang city, China. Results The major demographic characteristics among 2,676 VCT clients were: 41.1% were in the age range 20 to 30 years; 73.1% were males; and 67.1% had attained the level of junior high school education. The primary information source for VCT services was mass media like television (TV) and newspaper in 88.9%. 34.3% were afraid of the result of infection which was the main barrier to accept VCT services among 540 participants answering the question. 75.2% were motivated by recently acquired knowledge about HIV. 47.9% had 3 or more male sex partners, 62.3% had used condoms sometimes, and 14.5% had been infected with a STD. 2.8% of the participants identified themselves as men who have sex with men (MSM). The main demographic characteristics of MSM did not differ from the total group of participants except with respect to age: 63.5% reported having one male sex partner in the preceding 12 months, 44.6% reported never using condoms in the preceding 12 months, and only 2.7% reported a history of sexually transmitted disease. Conclusion Public education offered by health workers in hospitals, private clinics and other medical institutions needs to be strengthened. Given the results from this study, we recommend: (1) making VCT a routine part of health services, especially in areas where many high-risk individuals live; (2) improving the information sources and increasing the understanding of HIV and HIV-infected individuals; (3) enhancing international collaboration in strategic planning, technical assistance, and protocols to translate policy into effective action; (4) supporting Chinese non-government organizations (NGOs) in playing a significant role in the battle against AIDS.